Proteomic Analysis of Intracellular and Membrane-Associated Fractions of Canine (Canis lupus familiaris) Epididymal Spermatozoa and Sperm Structure Separation - Anna Zmudzinska; Mariusz A. Bromke; Rafal Strzezek; Magdalena Zielinska; Beata Olejnik; Marzena Mogielnicka-Brzozowska (Animals, 2022)
This study was provided for proteomic analysis of intracellular and membrane-associated fractions of canine (Canis lupus familiaris) epididymal spermatozoa and additionally to find optimal sonication parameters for the epididymal sperm morphological structure separation and sperm protein isolation. Sperm samples were collected from 15 dogs. Sperm protein fractions: intracellular (SIPs) and membrane-associated (SMAPs) were isolated. After sonication, sperm morphology was evaluated using Spermac Stain™. The sperm protein fractions were analyzed using gel electrophoresis (SDS-PAGE) and nanoliquid chromatography coupled to quadrupole time-of-flight mass spectrometry (NanoLC-Q-TOF/MS). UniProt database-supported identification resulted in 42 proteins identified in the SIPs and 153 proteins in the SMAPs. Differentially abundant proteins (DAPs) were found in SIPs and SMAPs. Based on a gene ontology analysis, the dominant molecular functions of SIPs were catalytic activity (50%) and binding (28%). Hydrolase activity (33%) and transferase activity (21%) functions were dominant for SMAPs. Bioinformatic analysis of SIPs and SMAPs showed their participation in important metabolic pathways in epididymal sperm, which may suggest their potential as sperm quality biomarkers. The use of sonication 150 W, 10 min, may be recommended for the separation of dog epididymal sperm heads, tails, acrosomes and the protein isolation.